2022
DOI: 10.1016/j.jvn.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on health lifestyle in patients with peripheral artery disease: A cross-sectional study

Abstract: Background Social isolation has been one of the main strategies to prevent the spread of Coronavirus 2019 (COVID-19). However, the impact of social isolation on the lifestyle of patients with peripheral artery disease (PAD) and claudication symptoms remains unclear. Objectives To analyze the perceptions of patients with PAD of the impact of social isolation provoked by COVID-19 pandemic on health lifestyle. Design Cross-sectional. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
(39 reference statements)
1
12
0
5
Order By: Relevance
“…Social isolation, because of the COVID-19 pandemic, has resulted in unintended consequences for the lifestyle and health of the population. 3 , 4 , 5 , 6 In the current study, the percentage of patients who self-reported practicing physical activity was similar between the two periods during the COVID-19 pandemic (28.3% [n=28] vs. 23.2% [n=23], P>0.05, respectively). We have previously demonstrated that the main barriers to physical activity practice in patients with PAD during the COVID-19 pandemic include social isolation, pain, injury or disability, lack of energy, and the need to rest because of leg pain.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Social isolation, because of the COVID-19 pandemic, has resulted in unintended consequences for the lifestyle and health of the population. 3 , 4 , 5 , 6 In the current study, the percentage of patients who self-reported practicing physical activity was similar between the two periods during the COVID-19 pandemic (28.3% [n=28] vs. 23.2% [n=23], P>0.05, respectively). We have previously demonstrated that the main barriers to physical activity practice in patients with PAD during the COVID-19 pandemic include social isolation, pain, injury or disability, lack of energy, and the need to rest because of leg pain.…”
Section: Discussionsupporting
confidence: 48%
“…The impact of physical activity on longitudinal changes in the self-reported health of patients with PAD was assessed through a questionnaire, as previously described. 5 , 6 , 13 The questionnaire was composed of questions divided into domains: (a) overall health, (b) physical health, (c) mental health, and (d) physical activity. The questions used in the analysis are presented below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Síntese dos estudos selecionados sobre os hábitos alimentares da população brasileira no período da pandemia da COVID-19. Em estudo realizado por Ritti-Dias et al (2022)(6), que objetivou analisar as percepções de pacientes com DAP sobre o impacto do isolamento social provocado pela pandemia de COVID-19 no estilo de vida saudável. Para tanto, este estudo foi realizado com 136 pacientes que possuem DAP, através de um questionário semiestruturado contendo perguntas relacionadas aos cuidados pessoais com COVID-19, saúde mental, hábitos de risco à saúde, comportamento alimentar, estilo de vida, atividade física, saúde geral e atenção à saúde das doenças arteriais periféricas.…”
unclassified